Effects of 810nm Diode Laser Irradiation on Flexural Strength of Dentin: An Invitro Study - Heshmat Mohajer, Amir Reza; Modaresi, Jalil; Molla, Reza; Ahmadi, Maryam; Rostami, Faramarz (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Thermal changes in laser assisted root canal therapy with the use of diode laser can predispose tooth structure to the fracture. This study evaluated the changes in flexural strength of dentin blocks after diode laser irradiations (810 nm). METHODS: A total of 60 dentinal blocks were prepared from freshly extracted teeth in three different thicknesses (300, 500 and 1000μm) and 20 sections in each of these thicknesses were divided randomly to the test and control groups. Samples in the test groups were irradiated at 2W power setting by scanning movement of 2mm/s of diode laser, and the controls were stored in normal saline. The flexural strength of samples was evaluated by UTM (Universal Testing Machine). Data analysis was done with the SPSS Software 11.5. RESULTS: Samples of 300μ had the lowest flexural strength (mean: 71/65 mpa) followed by 500 (116.64 mpa) and 1000μ (217.56 mpa). Statistical analyses showed that after laser irradiation, the flextural strength in the samples of 300μ was significantly lower than that in the other groups (500μ, 1000μ) (P= 0.017). CONCLUSION: Within the limits of this study, diode laser irradiation in laser assisted root canal therapy has no significant effect on flexural strength of root dentinal walls with the thickness of more than 500μ. Although in areas with critical dentinal width (≤300μ), this setting can jeopardize root micromechanical properties and predispose tooth to the root fracture.